Stromal CD4+ and CD8+ T Cells in Human Breast Carcinomas: Its Correlation with Chemokine MIG/CXCL9 - Laguens, Graciela (2012)
The interaction between some chemokines with tumoral and stromal cells can influence tumor progression. CXCL9, a monokine induced by interferon gamma (MIG), targets lymphocytes. The aim of our study was to identify and quantify CD4+ and CD8+ T cells in the stroma of human breast cancer and correlate them with the presence of MIG/CXCL9. In 58 specimens of human breast carcinoma and 10 normal breast tissue from mammoplasty surgery, immunohistochemis- try and ELISA methods were performed. The number of CD4+ and CD8+ T cells in breast cancer tissue was signifi-cantly increased compared with normal breast tissue with a clear predominance of CD8+ T cells. MIG/CXCL9 levels were significantly elevated respect normal breast tissue. This chemokine correlated with the number of CD8+ T cells only in non-metastatic tumors. These data suggest that MIG targets cytotoxic T cells. Their recruitment into breast car-cinoma can play a critical role in malignant progression, inhibiting the production of metastasis.